The Influence Of Audit Tenure, Auditor Reputation, Auditor Rotation, Audit Fee On Audit Quality - Virgiawan Deshandrio; Nadhif Rifadh Pasya; Irwan Sutirman Wahdiat (Jurnal Akuntansi, 2025)
This research aims to empirically examine the effect of audit tenure, auditor reputation, auditor rotation, and audit fee on audit quality in BUMN (State-Owned Enterprises in Indonesia) listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Audit quality is a key indicator of the reliability of financial statements and reflects the auditor’s ability to detect and report irregularities objectively. This study uses a quantitative approach with purposive sampling based on specific criteria: BUMN that consistently published complete annual reports and financial statements in Indonesian Rupiah during the observation period. The study results, obtained through logistic regression analysis, show that audit tenure and auditor rotation have a significant and positive impact on audit quality, suggesting that both longer engagement duration and proper auditor rotation enhance auditor performance and independence. In contrast, auditor reputation and audit fee do not significantly affect audit quality, indicating that affiliation with Big Four accounting firms or higher audit payments does not necessarily guarantee better audit outcomes. The regression model demonstrated good fit with a Nagelkerke R Square of 0.695, meaning the independent variables explain 69.5% of the variation in audit quality. These findings have practical implications for regulators and stakeholders in optimizing audit assignment policies to strengthen the quality of financial reporting. The research also highlights the need for greater oversight and accountability, particularly in the context of public companies. Future studies are encouraged to explore other factors that may influence audit quality using larger and more diverse samples.